Analysis of Musculoskeletal Disorders (MSDs) Complaints Among Shoe Production Workers and Posture Improvement Using the Posture Evaluation Index (PEI) - Pramesthi, Yanita Vidya; Tranggono, Tranggono; Sari, Rizqi Novita (Newinera Publisher, 2025)
This study aims to analyze Musculoskeletal Disorders (MSDs) complaints in shoe production workers at PT XYZ and evaluate work postures using the Posture Evaluation Index (PEI) approach. The methods used include data collection through direct observation, distribution of Cornell Musculoskeletal Discomfort Questionnaire (CMDQ), and posture assessment using OWAS, RULA, and REBA methods. The results showed that complaints most often occurred in the upper back, neck, and right shoulder, which were mostly caused by non-ergonomic work postures. The PEI assessment showed that the work section with the highest risk was the packing section, with a score of 2.7 indicating the need for immediate improvement. After improving the work posture according to ergonomic principles, the PEI score decreased to 1.6, indicating increased comfort and decreased risk of injury. This study emphasizes the importance of periodic ergonomic evaluations to improve work comfort and productivity.